2016
DOI: 10.1155/2016/3430285
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Walking Humans and Structures in Vertical Direction: A Literature Review

Abstract: Realistic simulation of the dynamic effects of walking pedestrians on structures is still a considerable challenge. This is mainly due to the inter- and intrasubject variability of humans and their bodies and difficult-to-predict loading scenarios, including multipedestrian walking traffic and unknown human-structure interaction (HSI) mechanisms. Over the past three decades, several attempts have been made to simulate walking HSI in the lateral direction. However, research into the mechanisms of this interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 58 publications
5
79
0
Order By: Relevance
“…given glass structure can be in fact affected by several parameters, like the loading features, the structural geometry, the properties of the involved materials and bonding layers or the presence of mechanical and adhesive restraints that could manifest a time/temperature/humidity-varying flexibility (see Figure 1 and [15,16]). Even more attention is required for pedestrian glass structures that could be subjected to severe operational conditions, with pronounced human structure interaction (HSI) phenomena [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…given glass structure can be in fact affected by several parameters, like the loading features, the structural geometry, the properties of the involved materials and bonding layers or the presence of mechanical and adhesive restraints that could manifest a time/temperature/humidity-varying flexibility (see Figure 1 and [15,16]). Even more attention is required for pedestrian glass structures that could be subjected to severe operational conditions, with pronounced human structure interaction (HSI) phenomena [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the dynamic performance under high crowd densities is often imperative for the design, these loading conditions have virtually never been verified [4]. Concerns about these load models are strengthened by the fact that recent studies indicate the significant impact of human-structure interaction (HSI) phenomena [5][6][7][8][9]. However, large-scale experimental evidence corroborating these results is absent.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the uncertainties of the estimated parameters and thus prevent an ill‐conditioned inverse problem, two measures were taken: (a) the FE model of the Viana footbridge was updated based on its experimental modal parameters estimated by operational modal analysis, and (b) a search domain was established for the parameters identification in each inverse problem. Each search domain was determined based on two aspects: (a) the results of previous studies reported in literature and (b) the knowledge of the physical problem. In next subsections, the identification process is described in detail.…”
Section: Experimental Estimation Of the Pedestrian Modal Parameters Imentioning
confidence: 99%